Tomato yield and soil chemical properties influenced by low–molecular–weight organic acids in calcareous soil - Pérez-Labrada, Fabián; Benavides-Mendoza, Adalberto; Juárez-Maldonado, Antonio; Solís-Gaona, Susana; González-Morales, Susana (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2024)
Calcareous soils have restrictive characteristics that limit and pose a challenge for crop production; in this environment, plants can exude low-molecular-weight organic acids (LMWOAs). This study aimed to verify the influence of exogenously applied LMWOAs in calcareous soils on tomato yield and the chemical characteristics of soil and leachate. Solanum lycopersicum L. seedlings were grown in pots containing calcareous soil in a greenhouse, fertilized by drip irrigation with Steiner nutrient solution in which the treatments 0.1 mM citric acid (CA), 0.1 mM oxalic acid (OA), 0.01 mM salicylic acid (SA) and a control without LMWOAs (T0) were prepared, applied during the whole growth cycle. The experiment was repeated four times, with twenty replicates per treatment, under a completely randomized design. The yield per plant was quantified, while pH and microbial respiration (RMS) were measured in the soil. The pH, electrical conductivity (EC), oxidation-reduction potential (ORP), carbonate (CO32–), and bicarbonate (HCO3–) contents were quantified in the leachates. SA application reduced the soil pH (8.75). SA and CA improved the fruit yield per plant by 11% and 33%, respectively (p < 0.05). CA induced a 1.7% reduction in leachate pH (p < 0.05) and a 15.9% increase in HCO3– content (p < 0.05). SA decreased EC and CO32– concentrations by 8.9 and 23.1% (p < 0.05), but increased HCO3– content by 23.1 % (p < 0.05). The use of LMWOAs as a strategy in the management of calcareous soils can promote favorable conditions for tomato yield per plant.